Strategi dan Tantangan Ekspor Makanan Ringan Resep Cau ke Malaysia: Analisis Bisnis Internasional - Hani Humaeriyah; Achmad Mansur Pauji; Annisa Pratiwi Sundari; Aufa Zulfikar Maulana; Fajar Yunawwirudin Haq; Muahammad Raka Alifian Firdaus; Wahidah Nazmi Lailia (PENG: Jurnal Ekonomi dan Manajemen, 2026)
Exporting snacks based on traditional recipes, such as "Resep Cau" (made from bananas), has significant potential to penetrate the Malaysian market, which shares similar tastes with Indonesia. This study aims to examine effective strategies and key challenges in exporting Resep Cau snacks to Malaysia within an international business context. The methods used were a desk study and qualitative analysis of relevant trade data, regulations, and export practices. The results indicate that prioritized strategies include product adaptation to local preferences, halal certification from a recognized Malaysian body, and optimization of distribution through digital platforms. Significant challenges include strict food import regulations, competition from local and Chinese products, and other non-tariff barriers